El síndrome del nido vacío y su influencia en los estados depresivos de padres con hijos que migran fuera del país, en los habitantes del cantón Chaguarpamba provincia de Loja, periodo 2014-2015 - Campoverde Luna, Katherine Paola (2015)
The purpose of this study was to identify how it influences the empty nest syndrome in depressive states of parents with children who migrate out of the country, talking about the people of Canton Chaguarpamba. The factors considered were the feelings about the empty nest, depression, anxiety, attachment styles and how to cope. One quantitative and qualitative research and descriptive type was carried out as scientific methods as they are: inductive deductive method, analytic-synthetic and empirical methods, which relied on the use of techniques such as the Beck test for depression, anxiety Hamilton Test and Lazarus coping scale, with the aim of analyzing the types of coping strategies developed by parents with children who have migrated abroad taking into account their appreciations and perceptions The main findings are that mild depression is the most common inhabitants of the canton Chaguarpamba with respect to the empty nest which is accompanied by a slight anxiety that does not interfere with the working lives of those affected and as to how syndrome coping strategy of escape and avoidance involving the use of strategies such as drinking, smoking, drugs , overeating , take drugs or sleeping more than usual is used. In general, pointing to ignore the problem. Key Words: Migration, feeelings, bound styles, coping, apreciations, perceptions.